(111) InAs/GaSb type‐II strained layer superlattice material for high operating temperature detection. Issue 5 (29th January 2013) - Plis, Elena; Klein, Brianna; Myers, Stephen; Gautam, Nutan; Krishna, Sanjay; Krishna, Sanjay; Plis, Elena
Abstract We report on the detailed radiometric characterization of the mid‐wave infrared InAs/GaSb type‐II strained layer superlattice detectors grown on GaSb (111) substrate. A red shift of 1.7 μm (at 295 K) was observed with respect to a similar detector grown on GaSb (100) substrate. We have measured, at 295 K and λ100% cut‐off = 5.6 μm, a dark current density of 0.53 A/cm2 (at ‐50 mV) and a Johnson noise limited D* of 8.5 x 109Jones, which are superior values to state‐of‐the‐art T2SL detectors with the same (pin) design grown on conventional GaSb (100) substrates and operating in a similar wavelength range. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)